Penegakan Hukum Terhadap Pelaku Tindak Pidana Pelecehan Seksual Melalui Media Sosial Dalam Pasal 27 Ayat 1 Uu Ite Nomor 19 Tahun 2016 - Kurniati, Kurniati (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Nowadays, crime is on the rise and one of them is verbal harassment on social media. Verbal harassment can happen in person, like whispering, screaming, and speaking. With technological advances, typing, sexuality, and sarcasm on social media (chats, direct messages, and comments) have become commonplace. Of course this shock is the same as a direct pursuit. Verbal harassment on social media is an illegal activity that violates article 27, paragraph 1, of the ITE Act, which does not specify specifically the type of abuse. Although the Covenant contains provisions on criminal offences, it is not well defined because the term harassment is not mentioned in the Convention. Lack of gender education is the primary cause of harassments, and on average, victims do not know that women are being harassed or committing suicide. Nowadays, there are many good laws in Indonesia, such as the KUHP and the ITE Act, which can hold verbal suicides criminally liable, even if they are far from perfect. This can be done by providing a legal framework for suicide and placing it in the category of violence.